2013
DOI: 10.1177/0361684313514855
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Masturbation

Abstract: With the present study, I explore the function, meaning, and empowerment potential of masturbation for 765 American women. The sample was somewhat diverse, but primarily young (79% under 30), White (75%), educated (85% with at least a bachelor’s degree), and heterosexual (67%). Participants completed an online anonymous survey that included endorsement of various attitudes toward masturbation, reasons for masturbating, and emotions following masturbation. Two split-half exploratory factor analyses (followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 53 publications
2
19
1
Order By: Relevance
“…Research has found associations between masturbation and negative outcomes, such as depression (Brody & Nicholson, 2013;Frohlich & Meston, 2002) and guilt (Bowman, 2014;Carvalheira & Leal, 2013). Bowman (2014) and Carvalheira and Leal (2013) found that women commonly reported shame or guilt as an emotional reaction to their masturbation, resulting in a decreased likelihood of positive physical and psychological outcomes associated with masturbation (Davidson & Darling, 1993). As masturbation is stigmatized by society, the guilt that results may be from the internalization of these messages, as opposed to the actual act of masturbation (Coleman, 2003).…”
Section: Masturbation As a Taboomentioning
confidence: 99%
See 4 more Smart Citations
“…Research has found associations between masturbation and negative outcomes, such as depression (Brody & Nicholson, 2013;Frohlich & Meston, 2002) and guilt (Bowman, 2014;Carvalheira & Leal, 2013). Bowman (2014) and Carvalheira and Leal (2013) found that women commonly reported shame or guilt as an emotional reaction to their masturbation, resulting in a decreased likelihood of positive physical and psychological outcomes associated with masturbation (Davidson & Darling, 1993). As masturbation is stigmatized by society, the guilt that results may be from the internalization of these messages, as opposed to the actual act of masturbation (Coleman, 2003).…”
Section: Masturbation As a Taboomentioning
confidence: 99%
“…Positive experiences with masturbation. Although some women report guilt and shame associated with their masturbation, positive experiences, such as empowerment, are also connected to women's masturbation (Bowman, 2014). Additionally, women who engaged in masturbation reported decreased difficulties in arousal and lowered sexual inhibition (Carvalheira & Leal, 2013).…”
Section: Masturbation As a Taboomentioning
confidence: 99%
See 3 more Smart Citations